(untitled) (Razão e Fé, 2026)
This article presents Max Scheler’s proposal for philosophical anthropology, focusing on the essential distinction between biopsychic life and the dimension of the Spirit (Geist). Based on the text The Human Place in the Cosmos, it investigates how the author seeks to overcome the fragmentation of historical conceptions through a phenomenological unity. The gradation of the levels of life is highlighted, starting from the affective impulse and passing through instinct and associative memory, up to practical intelligence, with the intent of demonstrating that the human distinctiveness is not merely a matter of evolutionary degree, but of essence. The conclusion explains that the human person is defined by three distinct forms: the capacity to objectify the world, autonomy from organic impulses, and the search for transcendence.